Baosteel Group : seeking strategic synergy through M&A integration - Xu, Jingyue, active 2016, (SAGE Business Cases., 2016)
As the most competitive iron and steel enterprise in China, Baosteel Group defined its strategy as "quality product plus scale economy" and has developed very fast since 2006. The basic developing model of Baosteel Group can be described as "expanding the scale by M&A," improving overall competitiveness by effective integration. This case analyzes two successful M&A cases of Baosteel-Bayisteel and Ningsteel; introduces their processes of M&A and integration thoroughly; and demonstrates the distinctive mode of Baosteel's M&A integration based on strategic synergy.